Case Report: Spontaneous lung intercostal hernia series and literature review - Ugolini, Sara; Abdelghafar, Moslem; Vokkri, Eduart; Sharkey, Annabel J.; Fontaine, Eustace; Voltolini, Luca; Morabito, Antonino; Ugolini, Dario; Granato, Felice (Frontiers in Surgery, 2023)
Spontaneous lung intercostal hernia (SLIH) is a rare condition potentially carrying severe morbidity. About 120 cases have been described so far, with an apparent increasing number of reports in recent years. The main presenting findings are chest pain and bulging, with ecchymosis in the affected area, hemoptysis, respiratory distress and signs of infection or incarceration being described as well. The gold standard treatment is not established, and conservative management has been advocated as first line for asymptomatic patients. We report a case series of 5 patients, in which 4 out of 5 patients, surgical repair was deemed necessary either at first evaluation or after failure of conservative management. One patient remains under surveillance and conservative management. We believe that SLIH surgical repair should be considered as first line for fit patients, due to the uncertainty of its mid- and long-term impact and described pejorative trend/defect enlargement. A proposed algorithm for SLIH management is also presented.